Mental health in the context of the family health program: social representations of users and family members - Vasconcelos, Mardênia Gomes Ferreira (2008)
The incorporation of mental health actions in basic attention enables better assistance coverage, with possibilities of prevention of mental illness and effective health promotion, avoiding isolation and prejudice, besides the acquisition of more humanized attitudes. This study aimed to explore the social representations of users and their relatives concerning mental health in the context of Basic Health Unity (BHU. The data were collected using the Free Word Association Test, processed on Tri-deux-mots software and interpreted through correspondence factor analysis. The research enabled to get closer to the community, in which latent and affective content of subjects were revealed, allowing thus, to draw a panorama of reality in basic attention through the representations about health, mental health, promotion of mental health, family and the Program Health of the Family.